Tempo livre da juventude de classe popular: desatando preconceitos e promovendo perspectivas positivas - Martins, Manoela Pagotto (2013)
The depiction of adolescence as a potentially problematic phase becomes more evident in the case of underprivileged teenagers, who carry with them the burden of belonging to a social class associated with crime and almost always risky and negative behavior, which contributes to characterizing them under a pessimistic light. In this sense, little has been said about the social and symbolic life of these teenagers and the studies that involve aspects related to their experiences in their free time have mainly focused on issues like abandonment, dangers and threats. Given this panorama, the general goal of this dissertation is investigating the many aspects related to the use of free time by teenagers from underprivileged classes. Thus, two studies were carried out with adolescents between 15 and 19 years old, from both genders, students attending public schools in the metropolitan area of the city of Vitória, in the state of Espírito Santo. In the first one, of a quantitative nature, a survey was conducted to assess these teenagers’ free time activities, their access to cultural goods, their participation in groups and the way they evaluate their interaction in the contexts of family, school and community. The data was collected via questionnaires and statistically analyzed by the SPSS software. Results have mainly hinted at the diversity of ways of spending free time among the surveyed adolescents and at the importance of social factors in the dynamics of their relationships. The second study, of a qualitative focus, is based on proximal processes proposed by the bioecological theory of human development, and aimed to investigate how the participation of teenagers from underprivileged classes in leisure groups (at church, sports clubs, dance clubs and others) can influence their development and the quality of their relationships with family and friends. The data was collected via interviews and categorized according to the PPCT model. The main results show that the interactions established by the teenagers within the groups promote positive changes in their personal characteristics and strengthen their relationship with their family and friends. In conclusion, the group has been a positive element in the lives of these teenagers and a favorable resource to their development.